WOŻĄC SAMOWARY DO TUŁY. CZY UDAŁO SIĘ POWIEDZIEĆ TO INACZEJ? - Garbol, Tomasz (Colloquia Litteraria, 2016)
The article’s starting point is the necessity to alter the paradigm of Polish poetry, which is declared in the ‘contemporary Polish lyric poetry’ anthology Powiedzieć to inaczej [To say it in a different manner]. The author attempts to assess the chance of the project’s success.